Weaving Production Monitoring System in Shuttleless Picanol Machine - Hananto, Agus; Wahidin, Didin; Zulfahmi, Muhammad; Oktavian, Dinan Safta (Sainteks: Jurnal Sain dan Teknik, 2025)
The development of the textile industry, especially the weaving industry, has been progressing, including quality performance, capacity expansion and production efficiency. One of the technological advances that has not been widely embedded in weaving production machinery is the technology related to the application of Industry 4.0, which has the main objectives of increasing production efficiency, reducing waste, and lowering production costs. In general, production equipment/machines in the textile industry, especially in the production of woven fabrics on shuttleless picanol machines, do not yet have a control system that can be used to build intelligence in the application of Industry 4.0. To be intelligent, these production machines need to be equipped with data processing modules, a series of sensors, and data processing systems. The development is carried out in stages, one of which is the monitoring system. Production monitoring was chosen because in the woven fabric manufacturing industry, production control and monitoring is a very important part of increasing production capacity and production efficiency, and supporting the application of Industry 4.0. This research focuses on designing and manufacturing a monitoring system for the production of woven fabrics, especially Picanol shuttleless weaving machines, which provides information services in the form of monitoring data on the amount of production, condition/status of machine operation, and consumption of electrical energy, displayed in graphical form (dashboard) in real time and can be accessed via a localhost network using a PC computer or smartphone web browser.